Participatory approaches and the measurement of human well-being - Sarah White; Jethro Pettit (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2004)
This paper considers the use of participatory methods in international development research, and asks what contribution these can make to the definition and measurement of well-being. It draws on general lessons arising from the project level, two larger-scale policy research processes sponsored by the World Bank, and the experience of quality of life studies. It also considers emerging experiments with using participatory methods to generate quantitative data. The paper closes by assessing the future trajectory of participatory approaches in well-being research, and reflects on some dilemmas regarding the use of participatory data on well-being in the policymaking process. – participation ; appraisal ; methodology
Keywords: I32; D63; R29; 330; Entwicklungsforschung